Dietary fiber and high-intensity interval training—two strategies to decrease obesity and improve MASLD and cardiometabolic health Ballaststoffe und Intervallausdauertraining – 2 Strategien zur Verbesserung von MASLD, Adipositas und kardiometabolischer Gesundheit - Reljic, Dejan; Herrmann, Hans Joachim; Zopf, Yurdagül (Die Gastroenterologie, 2025)
Dietary fiber plays a critical role in the prevention and management of obesity and its associated comorbidities including metabolic dysfunction-associated steatotic liver disease (MASLD). Fiber promotes satiety and intestinal motility, modulates postprandial glucose spikes, and reduces low-density lipoprotein (LDL) cholesterol levels. Epidemiological studies further indicate a protective effect of dietary fiber against cardiovascular diseases and colorectal cancer. Prebiotic fibers, such as inulin, positively influence the gut microbiome, which exerts systemic effects on the body through immunomodulatory mechanisms. A daily intake of ≥ 30 g of fiber is recommended, preferably achievable through the incorporation of whole grains, legumes, fresh fruits, and vegetables into the diet. To minimize gastrointestinal discomfort, fiber should be gradually introduced into meal plans. In addition to diet, physical activity is a cornerstone for improving cardiometabolic health. Low-volume high-intensity interval training (LOW-HIIT) offers an evidence-based, time-efficient alternative to traditional endurance training. LOW-HIIT combines short bursts of moderate-to-high intensity exercise with recovery intervals, performed in sessions lasting no more than 15 min. This approach has been shown to induce significant improvements in cardiorespiratory fitness, inflammation, and cardiometabolic risk markers within a few weeks. Thus, a fiber-rich diet coupled with regular LOW-HIIT represents a promising strategy for the prevention and treatment of obesity and metabolic syndrome.
CRIS-Team Scopus Importer:2025-03-21
Keywords: Exercise therapy; Fiber; Interval training; Metabolic syndrome; Metabolism